PENGARUH PEMBERIAN MINUMAN ISOTONIK TERHADAP HASIL PEMERIKSAAN KADAR BUN & KREATININ PADA MENCIT (MUS MUSCULUS) - Karimah, Akhlaqul; Nidianti, Ersalina (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Metabolism in the body is influenced by electrolytes. If the electrolyte concentration is abnormal, health problems will occur. Drinks that contain electrolytes are known as isotonic drinks. The kidneys are organs that play a role in body balance, such as controlling body fluids and maintaining the balance between acidic and alkaline compounds. It is important to check BUN and creatinine to determine kidney function. The aim of the research was to analyze the effect of giving isotonic drinks on the results of BUN and creatinine examinations in mice. This type of research is experimental which uses serum from test animals in the form of mice (Mus musculus). The test animals were divided into 5 groups and each group was treated for 14 days. Then after 14 days the test animals were sampled to check BUN and creatinine levels to determine the effect of giving isotonic drinks. All data is processed statistically using SPSS. The results of the ANOVA test obtained a Sig value. 0.878 on BUN levels and Sig values. 0.265 in creatinine levels. Conclusion: With the H0 criteria rejected if the significant value is 0.05 then H0 is accepted which can state that giving isotonic drinks with volumes of 0.5 ml, 0.8 ml and 1 ml has no effect on the results of checking BUN and creatinine levels.